2008
DOI: 10.1007/s10342-008-0246-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant species on physical, chemical and biological soil properties in a Mediterranean forest soil

Abstract: In semiarid ecosystems plant cover plays an important role in the improvement of physical, chemical and biochemical soil properties. With the aim of studying the influence of different plant species on soil properties, and establishing the relationships between them, 160 soil samples from under four different plant species (Pinus halepensis, Quercus coccifera, Juniperus oxycedrus and Rosmarinus officinalis) were taken in a forest area of the province of Alicante (SE Spain). The following soil properties were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…It may be concluded that the differences in enzymatic activity between the research plots result from different contents of PAHs and different amount of soil organic matter as a result of species composition. The chemical composition of SOM largely results from microbial transformation of tree litter, whose composition, in turn, influences the activity and diversity of soil microorganisms (Pérez-Bejarano et al 2010;Ushio et al 2008). Deciduous species had a positive impact on soil organic matter and the most beneficial impact on the intensification of microbial activity.…”
Section: Discussionmentioning
confidence: 99%
“…It may be concluded that the differences in enzymatic activity between the research plots result from different contents of PAHs and different amount of soil organic matter as a result of species composition. The chemical composition of SOM largely results from microbial transformation of tree litter, whose composition, in turn, influences the activity and diversity of soil microorganisms (Pérez-Bejarano et al 2010;Ushio et al 2008). Deciduous species had a positive impact on soil organic matter and the most beneficial impact on the intensification of microbial activity.…”
Section: Discussionmentioning
confidence: 99%
“…SOM pools are also increased by leaves' senescence, and by animals returning undigested fiber to the soil. The stability of SOC pools established in SBPPRL depends on landscape factors (Pérez-Bejarano et al, 2010). Non-labile fractions (lower decomposition rates) are higher when the pasture is installed in forested areas (Ramachandran Nair et al, 2009).…”
Section: Proposed Ecological and Economic Effects Of Sbpprlmentioning
confidence: 99%
“…Many works are focused on studying the effect of woody plants on the formation and properties of the forest floor (e.g. Augusto et al 2003;Ritter et al 2003;Hagen-Thorn et al 2004;Pérez-Bejarano 2010;Kacálek et al 2013;Ulbrichová et al 2014). Studies dealing with herbaceous species beneath forest stands are scarce, mostly concerning the species abundance in relation to tree layer parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%